2020
DOI: 10.3390/w12071902
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Assessment of TRMM and GPM-Based Precipitation Products in Transboundary River Catchment (Chenab River, Pakistan)

Abstract: Water resources planning and management depend on the quality of climatic data, particularly rainfall data, for reliable hydrological modeling. This can be very problematic in transboundary rivers with limited disclosing of data among the riparian countries. Satellite precipitation products are recognized as a promising source to substitute the ground-based observations in these conditions. This research aims to assess the feasibility of using a satellite-based precipitation product for better hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 75 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…The correlation coefficients between all three different combinations, the CRU TS3.1 and measurement-based datasets, CFSR and measurement-based datasets, as well as APHRODITE_ V1101 and measurement-based datasets, showed a good performance, meaning that they could be used for hydrological modeling in the UVRB. In many studies, Taylor diagrams have been applied to evaluate the performance of satellite products against observational datasets [75,76].…”
Section: Resultsmentioning
confidence: 99%
“…The correlation coefficients between all three different combinations, the CRU TS3.1 and measurement-based datasets, CFSR and measurement-based datasets, as well as APHRODITE_ V1101 and measurement-based datasets, showed a good performance, meaning that they could be used for hydrological modeling in the UVRB. In many studies, Taylor diagrams have been applied to evaluate the performance of satellite products against observational datasets [75,76].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, numerous studies have compared the reliability of the GPM-based and other precipitation series on daily and monthly timescales (Lu et al 2018;Su et al 2019;Xu et al 2019;Ahmed et al 2020). For instance, Ahmed et al (2020) compared the daily-based precipitation products (IMERG-F and TRMM (3B42V7)) over the Chenab River catchment and found that IMERG-F has better performance than 3B42V7 for the simulation of daily and monthly flows.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods have high uncertainty in soil properties estimation because there is a wide range of properties for soils with a similar taxonomy (Di and Kemp 1989;Quesada et al 2010;Narasimhan et al 2012). Global weather data for SWAT (CFSR 2019) or remotely sensed satellite data (e.g., Ercan et al 2015) are often used to overcome the weather data scarcity problem (Dile and Srinivasan 2014;Ahmed et al 2020). But these coarse data sets cannot capture the extreme variability with topography in places like the Peruvian Andes.…”
Section: Introductionmentioning
confidence: 99%